Soil fertility management for productivity enhancement of jute under some constrained acidic soils of West Bengal - MAJI, B; SAHU, N C; DAS, I; SAHA, S; SARKAR, S; SAHA, SUPRAKASH (The Indian Journal of Agricultural Sciences, 2012)
Jute crop plays a pivotal role in the farming economy of number of eastern Indian states like West Bengal (Paschimbanga), Asom, Bihar and Odisha. In spite of available sound production technology, the main concern in jute fibre production system in India is the non-uniform productivity over 87 jute-growing districts located in varying agro- climatic regions of the country including 17 jute-growing districts of West Bengal having relatively higher productivity in South Bengal than in North Bengal. The major reasons of technical nature for low productivity in North Bengal are initially identified as soil acidity. The participatory farmers’ field experiments were conducted at Balurghat (pH 5.06, EC 0.024 dS/m, OC 0.59%, available N, P, K= 246, 29, 90 kg/ha) and Kumarganj (pH 4.45, EC 0.002 dSm-1, OC 0.51%, available N, P, K= 314, 15, 98 kg/ha) blocks of Dakshin Dinajpur district of North Bengal with an aim to enhance the productivity of jute through proper soil fertility management. The results of the field experiment revealed that application of lime (based on LR value) coupled with soil test-based balanced fertilization enhanced the productivity of olitorius jute [over farmers’ practice Balurghat [(2.42 tonnes/ha) and Kumarganj (1.52 tonnes/ha)] by 29.1% and 45.7% in the constrained acidic block of Balurghat and Kumarganj (of Dakshin Dinajpur district) respectively. The same treatments also improves the B:C ratio and reduced insect pests and disease incidence.